Parent-Teacher Interaction System: Development of Parent-Teacher Communication and Collaboration System - Kinn Abass Bakon,; Noureddon Beleid,; Zureen Zakaria, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study seeks to enhance communication and collaboration between parents and teachers in primary schools. The research delves into the myriad challenges parents and teachers encounter when attempting to communicate and collaborate effectively, particularly in the context of busy schedules and the absence of a dedicated platform. To address these issues, the aim of this study is to propose a "Parent-Teacher Interaction System (PTIS)," a comprehensive web-based platform designed to bridge the communication gap and support collaborative efforts between parents and teachers. The development of PTIS follows an agile software development methodology, ensuring that the platform is both adaptable and user-centric. The system offers a suite of features such as real-time tracking of student performance across academics and activities, a structured feedback mechanism for parents, multilingual support, a PTIS chatbot for instant queries, daily attendance monitoring, and detailed attendance reports. Beyond serving its immediate users, the PTIS is envisioned as a model for future research and development initiatives aimed at creating educational tools that enhance parent-teacher engagement and ultimately contribute to the betterment of student outcomes. تسعى هذه الدراسة إلى تعزيز التواصل والتعاون بين الآباء والمعلمين في المدارس الابتدائية. ويتناول البحث التحديات العديدة التي يواجهها الآباء والمعلمون عند محاولة التواصل والتعاون بشكل فعال، وخاصة في سياق الجداول الزمنية المزدحمة وغياب منصة مخصصة. ولمعالجة هذه القضايا، يهدف هذا البحث إلى اقتراح "نظام تفاعل الآباء والمعلمين"، وهو عبارة عن منصة شاملة تعتمد على الويب ومصممة لسد فجوة الاتصال ودعم الجهود التعاونية بين الآباء والمعلمين. ويتبع تطوير نظام تفاعل الآباء والمعلمين منهجية تطوير برمجيات مرنة، مما يضمن أن تكون المنصة قابلة للتكيف وتركز على المستخدم. ويقدم النظام مجموعة من الميزات مثل التتبع الفوري لأداء الطلاب عبر الأنشطة والدراسات الأكاديمية، وآلية ردود الفعل المنظمة للآباء، والدعم متعدد اللغات، وبرنامج محادثة تفاعلي للاستفسارات الفورية، ومراقبة الحضور اليومي، وتقارير الحضور التفصيلية. وبعيدًا عن خدمة مستخدميه المباشرين، يُنظر إلى نظام تفاعل الآباء والمعلمين باعتباره نموذجًا لمبادرات البحث والتطوير المستقبلية التي تهدف إلى إنشاء أدوات تعليمية تعزز مشاركة الآباء والمعلمين وتساهم في نهاية المطاف في تحسين نتائج الطلاب